Comparative evaluation of accuracy of different generations of electronic apex locator in determining the correct working length: A systematic review and meta-analysis - Pooja Sunil Bhagat; Vibha R Hegde; Sahil Kawle; Pritisha Bharat Jain (Wolters Kluwer Medknow Publications, 2023)
Aim: Different approaches are used to determine the working length of the root canal. The current and most widely researched are the electronic apex locators (EALs). Since the early apex locators were developed in 1942, several generations had their qualities and shortcomings developed. Thus, a comparative evaluation of the accuracy of different generations of EALs in determining the correct working length: Systemic review and meta-analysis to analyze individual studies quantitively and draw conclusions on the best generation of apex locator currently used. Materials and Methods: A comprehensive search was conducted on different electronic databases and by manual search. Studies comparing third and fifth generations with fourth-generation apex locators were subject to strict inclusion criteria followed by data extraction and meta-analysis. Results: Following the meta-analysis, the accuracy is fifth>fourth>third generation of apex locators. Conclusion: Analysis of individual studies quantitatively will give a better understanding of which devices to use to accurately determine the working length.